Hot on RAD51C: structure and functions of RAD51C‐XRCC3 - Barnabas Szakal; Dana Branzei (Molecular Oncology, 2023)
A new study by Longo, Roy et al. has solved the structure of the RAD51C‐XRCC3 (CX3) heterodimer with a bound ATP analog, identifying two main structural interfaces and defining separable replication fork stability roles. One function relates to the ability of RAD51C to bind and assemble CX3 on nascent DNA, with an impact on the ability of forks to restart upon replication stress. The other relates to effective CX3 heterodimer formation, required for 5′ RAD51 filament capping, with effects on RAD51 filament disassembly, fork protection and influencing the persistence of reversed forks.